Recurrent Pneumonitis in Patients with Melanoma Treated with Immune Checkpoint Inhibitors. (18th February 2019) - Asher, Nethanel; Marom, Edith M.; Ben‐Betzalel, Guy; Baruch, Erez Nissim; Steinberg‐Silman, Yael; Schachter, Jacob; Shapira‐Frommer, Ronnie; Markel, Gal
Abstract: Introduction: Immune checkpoint inhibitors (ICIs) have changed the oncologic landscape in the past few years. Alongside impressive antitumor responses, new novel immune‐related adverse events (irAEs) have emerged; pneumonitis is an irAE that can potentially be fatal and necessitates a proper management. No consensus exists regarding steroid treatment duration or drug rechallenge options. Our study describes the clinical and radiological course of melanoma patients diagnosed with immune‐related pneumonitis that has recurred because of rechallenge attempt or despite complete treatment discontinuation (unprovoked). Materials and Methods: The study population was composed of patients with metastatic melanoma who were treated with anti‐programmed cell death 1 (PD‐1) as monotherapy or in combination with anti‐cytotoxic T lymphocyte antigen‐4 and who were diagnosed with immune‐related pneumonitis. For recurrent cases after clinical and radiological resolution, we explored the differences from cases with no recurrence. Results: Nineteen out of 386 (4.8%) patients treated with ICI were diagnosed with pneumonitis. Median age was 66 years, and 53% were male. Compared with single‐agent nivolumab, patients treated with ipilimumab‐nivolumab combination presented with an earlier onset (27.5 vs. 10.3 weeks, respectively, p = .015) and had higher grades of severity. After complete resolution, rechallenge was attempted in seven patients; three of them had recurrent pneumonitis. Three other patients experienced recurrent pneumonitis despite complete discontinuation of the drug (unprovoked by rechallenge). The latter were characterized with an earlier onset of the first pneumonitis compared with those who did not experience recurrence (median, 12.4 vs. 26.4 weeks) and a shorter course of steroid treatment at first episode (median, 5.1 vs. 10 weeks). Recurrent cases were generally more severe than the first episode. Conclusion: Unprovoked recurrent pneumonitis is a new, poorly reported entity that requires further investigation. Our observations suggest that cases of pneumonitis that present early in the course of immunotherapy treatment may recur despite treatment discontinuation, thus necessitating closer monitoring and a longer course of steroid treatment. Abstract : Immune checkpoint inhibitors are associated with a unique profile of adverse events that can affect many organ systems. One of them is immune‐mediated pneumonitis — an uncommon adverse event that might be life threatening. Up to date, no consensus exists regarding immunotherapy rechallenge in these cases. This article evaluates the clinical and radiological characteristics of patients with metastatic melanoma who experienced recurrent immune‐related pneumonitis with or without treatment rechallenge.